NILAI PENDIDIKAN KARAKTER PADA TEMA DIRIKU KELAS 1 SD/MI DALAM BUKU TEMATIK KURIKULUM 2013 - Kumalasari, Yuli (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The aim of this research is to determine the character education values contained in the independent theme books for grade 1 SD/MI in the 2013 curriculum thematic books. My theme. The results of the research show that 1) the character education values contained in the self theme in the 2013 curriculum class 1 thematic book include being friendly and communicative, tolerance, social care, and love of peace. 2) application of the value of self-themed character education in the 2013 curriculum class 1 thematic books through familiarization and extracurricular activities